The reaction between oxygen, O2, and hydrogen, H2, to produce water can be expressed as,
2H2 + O2 --> 2H2O
The masses of each of the reactants are calculated below.
2H2 = 4(1.01 g) = 4.04 g
O2 = 2(16 g) = 32 g
Given 1.22 grams of oxygen, we determine the mass of hydrogen needed.
(1.22 g O2)(4.04 g H2 / 32 g O2) = 0.154 g of O2
Since there are 1.05 grams of O2 then, the limiting reactant is 1.22 grams of oxygen.
<em>Answer: 1.22 g of oxygen</em>
????????????????????????????????????????????????????
A positive cahnge of enthalpy, ΔH rxn = + 55 kJ/mol, for the forward reaction means that the reaction is endothermic, i.e. the reactants absorb energy and the products are higher in energy.
Activation energy is the difference in the energy level of the reactants and the peak in the potential energy diagram (the energy of the transition state).
For an endothermic reaction, the products will be closer in energy to the transition state than what the reactans will be; so, the activation energy of the reversed reaction is lower than the activation energy of the forward reaction.
Activation energy of reverse and forward reactions is related by:
Activation energy of reverse rxn = Activation energy of forward rxn - ΔH rxn
=> Activiation energy of reverse rxn = 102 kJ/mol - 55 kJ/mol = 47 kJ/mol
Answer: 47 kJ/mol
Answer:
The number of sulfur atoms in 1 g of sulfur is:-
atoms
Explanation:
Avogadro’s number represent the number of the constituent particles which are present in one mole of the substance. It is named after scientist Amedeo Avogadro and is denoted by
.
Avogadro constant:-

Given atomic mass of sulfur = 32 u
Which means that:-
32 g of sulfur contains
of atoms
Also,
1 g of sulfur contains
of atoms
<u>So, The number of sulfur atoms in 1 g of sulfur is:-
atoms</u>
Answer:
8.88 x 10⁻² M/s
Explanation:
The rate of reaction for:
NO(g) + Cl₂ (g) ⇒ 2NOCl(g)
is rate = -ΔNO/Δt = -ΔCl2/Δt = 1/2 ΔNOCl/Δt
so ΔNOCl/Δt = 2 ΔCl2/Δt = 2 x 4.44 × 10⁻² M/s = 8.88 x 10⁻² M/s
In general given a reaction
aA + bB ⇒ cC + dD
rate = -1/a ΔA/Δt = -1/b ΔB/Δt = 1/c ΔC/Δt = 1/d ΔD/Δt